Analisis Penggunaan Instagram sebagai Media Pemasaran Pada Perusahaan DE Plafon - Rio, Firstan; Paramita, Mellita; Thang, Susanti (Fakultas Komputer - Universitas Universal, 2021)
This study aims to determine the use of Instagram as marketing for DE Plafon company. Qualitative methods were used in this study, with data sources derived from primary data that used observation methods and secondary data that used interview methods. Observation was used to gain October and November 2021 insight data such as Profile Activity, Content Reach, and Reached Audience from DE Plafon Instagram, while interview was used to gain data about DE Plafon from one of the DE Plafon employees. The end result of this study is to showed how effective Instagram as marketing for DE Plafon and suggestion for DE Plafon.